2003
DOI: 10.1046/j.1460-9592.2003.t01-1-00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Performance of Steroid‐Eluting Epicardial Leads in a Growing Pediatric Population:

Abstract: Patient size and congenital heart defects complicate pacemaker therapy in children favoring an initial epicardial approach. Steroid-eluting (SE) epicardial (EPI) leads maintain stable, low pacing thresholds in the short-term when compared to the nonsteroid (NSE) epicardial (EPI) leads. The purpose of this study was to evaluate chronic, 10-year performance of SE leads in growing children compared with NSE EPI leads implanted during the same time interval. From 1990 to 2000, 35 patients (age 1 month to 18 year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 17 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…However, in the presence of (relative) contraindications for the transvenous approach, such as small body size, an intra-cardiac shunt or absence of a venous access, an epicardial lead implantation is preferred despite the high rate of lead failure. The estimations of lead longevity vary widely, and seems to be difficult to predict whereas different risk factors for lead failure had been described [3][4][5][6][7][8][9][10]. In our study, we found an incidence of lead failure of 2.3% per lead per year of follow-up.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, in the presence of (relative) contraindications for the transvenous approach, such as small body size, an intra-cardiac shunt or absence of a venous access, an epicardial lead implantation is preferred despite the high rate of lead failure. The estimations of lead longevity vary widely, and seems to be difficult to predict whereas different risk factors for lead failure had been described [3][4][5][6][7][8][9][10]. In our study, we found an incidence of lead failure of 2.3% per lead per year of follow-up.…”
Section: Discussionmentioning
confidence: 59%
“…Lead failure occurred in 7.4%, with an estimated freedom from lead failure after 5 years of 58% [1]. In another study by Horenstein et al 62 children with a median age of 5.2 years received 79 epicardial leads [10]. During a median follow-up of 6 years a lead fracture occurred in Data are presented as number (percentage) or mean ± standard deviation CHD congenital heart disease; cm centimetres 7.6% of the implanted leads [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps a more guided approach such as that suggested by Dekker et al using intra-procedural pressurevolume loop monitoring may have altered the outcome (25). Epicardial pacing systems have been more frequently associated, than transvenous systems, with higher pacing thresholds, diaphragmatic stimulation, lead fracture and insulation breaks (26).The use of steroid eluting leads, does alleviate some of the deterioration in pacing parameters but this unfortunately did not offer an advantage in the second patient (27). Due to previous surgery, the location of viable myocardium for pacing is difficult and www.intechopen.com…”
Section: Casementioning
confidence: 99%
“…However,since the introductionofnewer, steroid-eluting epicardial leads, therehas been asignificant improvement in follow up outcome to an extent that epicardial leads can now be considered similar in performance to transvenous leads (29,30). The steroid tip reduces inflammation at the interface between lead and tissue and has been demonstrated to keep electrical thresholds lower than conventional epicardial leads, both in the short term and long term (31).C ertain epicardiall eads now haves utureless fixation, with asimple screw in mechanism required to position the lead tip (eg: Myodex Epicardial Lead, St Jude Medical, St. paul, Minnesota, USA). An ex-ample of one of these leads can be seen in the postimplantation chest x-ray of Fig.…”
Section: Epicardial Pacing Leadsmentioning
confidence: 99%